Robust RAM Control for WSR on the Water Surface - Chun, K; Kim, B (International Journal of Engineering and Technology, 2018)
This paper discusses a robust rotate and move (RAM) controller by considering a water striding robot (WSR) with two wheels. The proposed controller commands the WSR to rotate and move straight toward the desired target by considering the two wheel WSR characteristics. Sliding mode control (SMC) is one of the solutions in nonlinear controller design and it has fast response and robustness. SMC is applied to the WSR RAM control. However, the sliding mode has a problem called chattering because of using sign function in controller design and this will cause the system unstable in WSR control because the chattering make the WSR sink into water easily. As a solution, sign function is replaced by saturation function. The proposed controller is noble and track the target point easily and also has robustness. The stability of the proposed controller is proved by Lyapunov function and the simulation results show the fast response and robustness.Â Â